Dimensional characteristics of FDM 3D printed PEEK implant for craniofacial reconstructions (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing (AM) or three-dimensional (3D) printing is rapidly gaining acceptance in craniomaxillofacial surgeries. Polyetheretherketone (PEEK) patient-specific implants (PSIs) have been used, mainly in reconstructive surgeries, as a reliable alternative to other alloplastic biomaterials. With the use of Fused Deposition Modeling (FDM) 3D printing technology, complex anatomical shaped PEEK PSIs can be fabricated within a clinically acceptable dimensional accuracy range and in a short time-frame. This aspect paves the way for prospective clinical applicability, especially in an in-house 3D printing set-up, where hospitals can utilize this digital AM workflow to provide personalized treatments cost-effectively.
Keywords: craniomaxillofacial surgeries; workflow; PEEK; FDM